OVERCOMING THE AGGRESSIVE BEHAVIOR OF THE BULLYING THROUGH GESTALT COUNSELING APPROACH - Fauzan Habibie Nasution; Netrawati (Yayasan Citra Dharma Cindekia, 2021)
Overcoming aggressive behavior of bullying behavior through gestalt counseling approach with empty chair technique. In today's digital era, this bullying process can be categorized as aggressive behavior. This type of research is this type of research is used in research in the form of library research (Library search) Literature study, This research uses action (action research) The results showed that there was a decrease in the presentation level of the client's aggressive behavior during and after being given gestalt counseling with the empty chair technique. that the client's aggressive behavior before being given gestalt counseling with the empty chair technique. Before gestalt counseling with the empty chair technique was carried out aggressive behavior bullying was still a habit for those who did it. By providing gestalt counseling with the empty chair technique, it can reduce the percentage of aggressive bullying behavior, Gestalt counseling also provides understanding to clients so that they can think, and can empathize and are able to understand other people and perpetrators are expected to be able to control their emotions so they don't vent to anyone. By acting as a top dog and under dog, the perpetrator can break the chain of his past so that the perpetrator can control his emotions.